2020
DOI: 10.1039/c9gc02567g
|View full text |Cite
|
Sign up to set email alerts
|

Flame-made amorphous solid acids with tunable acidity for the aqueous conversion of glucose to levulinic acid

Abstract: Composition-tunable mixed Brønsted/Lewis acids on silica-alumina and silica-alumina-phosphate prepared by the rapid flame spray pyrolysis produce exceptionally high glucose-to-levulinic acid yield, twice that of commercial ZSM-5 and Zeolite X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…However, a substantial yield of FA (ca. 6–7 C mol % at 130 °C, 15–20 min) was detected in the EC/H 2 O solvent, possibly inferring the yield of LA in the solvent system as LA and FA are coproduced during the catalytic conversion of biomass and sugars. ,, A schematic presentation of the reaction pathways for acid-catalyzed paper towel conversion in carbonate solvent/H 2 O is illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…However, a substantial yield of FA (ca. 6–7 C mol % at 130 °C, 15–20 min) was detected in the EC/H 2 O solvent, possibly inferring the yield of LA in the solvent system as LA and FA are coproduced during the catalytic conversion of biomass and sugars. ,, A schematic presentation of the reaction pathways for acid-catalyzed paper towel conversion in carbonate solvent/H 2 O is illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Among them, SAPO molecular sieves stand out for their ultra-high (hydro)thermal stability, original porosity, tunable acidity, and hydrophilicity. 23,24 Notably, as the most important representative of SAPOs, the small-pore SAPO-34 with 8-membered ring (8-MR) channels and CHA cages exhibits unanticipated catalytic performance in the dehydration of carbohydrates to high-valued platform chemicals. Dhepe et al first disclosed that SAPO-44 (analogue of showed superior catalytic activity compared with conventional aluminosilicate (beta, MOR and USY) and other SAPO catalysts (SAPO-5, SAPO-11, and in the conversion of softwood hemicellulose to furfural reaction, and 63% yield of furfural could be achieved in the toluene/H 2 O biphasic system.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Hydrolysis of cellulose and lignocellulose into LA can be catalyzed by enzymes, [15,16] mineral acids, [17][18][19] Lewis acids, [20] and solid acids. [21][22][23] Enzymatic hydrolysis is an efficient strategy as it takes place under gentle conditions and causes few side reactions. Unfortunately, enzymes are prone to contamination during the reaction and are limited by high costs.…”
Section: Introductionmentioning
confidence: 99%